Development of renewable thermosetting polymers based on grape seed oil derivatives. Issue 41 (12th August 2022) - Gaglieri, Caroline; Alarcon, Rafael Turra; Magri, Raquel; North, Michael; Bannach, Gilbert
Abstract: The demand for polymeric materials increases year by year, and most of them are derived from nonrenewable sources, and their consume has been increasing year by year. Therefore, there is a demand for research on bioderived polymers that are viable to be produced on an industrial scale. Based on the lack of polymers produced exclusively using monomers derived from vegetable oils, this paper shows the syntheses of renewable thermosetting polymers derived exclusively from grape seed oil, which is a by‐product from the wine and grape juice industries. After the evaluation of the effect of using or not catalyst, it was determined that increasing 1‐methylimidazole amount in the monomer mixture provides the decreasing of parallel reactions. However, thermal and mechanical properties, as well as the crosslinking density of polymers do not change significantly using 1.0% or 5.0% of catalyst (the minimal amounts needed to favor the esterification). Based on the characterization, the final polymers are not favorable in applications that require high mechanical impacts. However, they would be excellent as coatings due to their elevated crosslinking density, hydrophobic properties and homogenous surface. In addition, based on the properties observed under UV‐light, they can also be used as luminescent materials. Abstract : Renewable polymers were obtained from two grape seed oil monomers using different catalysts and also in absence of them. 1Im was the most selective catalyst and using 5.0 mol% was enough to almost suppress the etherification reaction. However, using 1% or 5% of 1Im did not change significantly the polymers final properties.